The mediating role of job satisfaction on the relationship between workplace stress and turnover intention - Foo, Alexander Hong Leong (2023)
This study examines the effect of workplace stress, job satisfaction, and turnover intention among academic staff of private universities. The high turnover intention of academic staff caused many negative impacts on universities, including the quality of education provided. Workplace stress has always been a problem among academicians, especially in the private sector. From a population of 48,643 academic private university staff in Malaysia, a sample size of 110 academic staff was obtained using G-power. Questionnaires were distributed to the academic staff through email as well as face-to-face distribution. The Workplace Stress Scale, Job Satisfaction Scale, and Turnover Intention Scale were used to measure each variable, respectively. The data collected was then analyzed through multiple regression using SPSS to determine the predicting effects of workplace stress and job satisfaction towards turnover intention. Based on the findings, it was found that turnover intention was positively predicted by workplace stress and negatively predicted by job satisfaction, workplace stress negatively predicted job satisfaction, and satisfaction partially mediated the relationship between workplace stress and turnover intention. This study has contributed to the current literature by highlighting the essential effects of workplace stress and job satisfaction in determining turnover intention and indicating that job satisfaction mediates the relationship between workplace stress and turnover intention. The study also allowed for better insight and greater awareness of employers in private universities towards the importance of reducing workplace stress and ensuring high levels of job satisfaction among staff